Morphological characterization of elite cacao trees (Theobroma cacao L.) in Tumaco, Nariño, Colombia - Ballesteros P., William; Lagos B., Tulio César; L., Hugo Ferney (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2016)
The cacao has become an essential part of the fight against the effects of illegal crops and rural poverty in Colombia. Because of their bromatological characteristics, cocoa beans are preferred in markets. However, there are few studies on the variability of the regional genotypes. The goal of this study was to characterize the cacao trees in Tumaco, Nariño (Colombia) and establish their morpho-agronomic variability. Plant collections were conducted in five production zones of the municipality between 0 to 270 m. On each farm, the productivity and plant health variables were recorded for the outstanding plants. The characterization was carried out using a Principal Component Analysis (PCA), Multiple Correspondence Analysis (MCA) and Cluster analysis. In the PCA, the first five components explained 70.2% of the variation. The first three components were characterized by productivity, while the last two components showed a low pod and grain index. In the MCA, the first three factors expressed 39.5% of the variation. The first three corresponded to the cundeamor cacao, acute pod apex, absence of anthocyanin in ripe fruits, without notable pulvinus, staminodes without anthocyanins, and moderately susceptible to Moniliophthora perniciosa. The last two components reported tolerance to M. roreri and Crinnipellis perniciosa, intense anthocyanin pigmentation on the floral buttons and Angoleta-shaped fruit. The selected genotypes showed important characteristics that must be analyzed with molecular and sensorial analyses.